Enhancing Competitiveness: A Key Challenge of Globalisation - Uppal, R. K.; Kumar, Navdeep (Indian Journal of Marketing, 2008)
The invocation of the forces of globalisation has exacerbated the pace of market competition. Globalisation has become an irresistible and irrevocable feature of the 21st century. Globalisation hings on free trade and therefore upholds the principle of competitiveness. The competitiveness of an open economy is the hallmark of its success in the era of globalisation. In open market competition, every organisation has to face stiff challenges and the success and survival of an organisation largely depends upon the competitiveness. Competitiveness refers to the characteristics that permit a firm to compete efficiently. It indicates the capabilities of a firm or a sector or a nation to compete successfully. Competitiveness is not merely a question of having free markets, rather there are many factors ranging from macro economic policies, presence of institutions, the educational system to micro policies at the level of the firm, that augment the capabilities and hence, the competitiveness. An appropriate competitiveness strategy, tailor-made to national conditions and development objectives is a vital ingredient of successful adjustment in the face of rapid globalization. Competitiveness is a multidimensional concept in the sense that being competitive requires superiority in several aspects. The present paper focuses on various issues relating to the competitiveness and suggests some strategies for enhancing the competitiveness of an organisation in order to compete efficiently in the globalised competitive environment.